2023
DOI: 10.28982/josam.7673
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selenium levels between diabetic patients with and without retinopathy

Abstract: Background/Aim: Diabetic retinopathy is a common ailment that causes visual impairment among adults, and evidence suggests that oxidative stress plays a significant role in its pathogenesis. The objective of this study was to examine the potential association between selenium deficiency and an increased risk of diabetic retinopathy among individuals with type 2 diabetes mellitus. Methods: This study was a prospective case-control study. 115 patients with a diagnosis of type 2 diabetes mellitus were included. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Various retrospective studies investigating the correlation between plasma selenium and the risk of DR have produced conflicting findings. For instance, Kurt et al [ 33 ] observed that patients with diabetic retinopathy had lower plasma selenium levels compared to the control group, whereas Wang et al [ 34 ] found significantly higher plasma and vitreous selenium concentrations in DR patients compared to control patients. Additionally, in a cross-sectional study of the United States population, selenium was found to be positively associated with diabetes but inversely associated with all-cause mortality [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various retrospective studies investigating the correlation between plasma selenium and the risk of DR have produced conflicting findings. For instance, Kurt et al [ 33 ] observed that patients with diabetic retinopathy had lower plasma selenium levels compared to the control group, whereas Wang et al [ 34 ] found significantly higher plasma and vitreous selenium concentrations in DR patients compared to control patients. Additionally, in a cross-sectional study of the United States population, selenium was found to be positively associated with diabetes but inversely associated with all-cause mortality [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This stress is a key contributor to neovascular unit insults, underpinning the core pathophysiology of PDR. Additionally, diabetic patients are more susceptible to oxidative stress due to impaired defense mechanisms, further emphasizing the role of oxidative stress in the development and progression of diabetic retinopathy, including PDR (8).…”
Section: Introductionmentioning
confidence: 99%